El muralismo zapatista: Una revuelta estética. - i Puig, Salvador Martí (Latin American Research Review, 2022)
This article deals with how Zapatismo has aesthetically addressed its political transformation and the aesthetic fruits it has achieved. To this end, the text interprets how the Zapatista identity has been created and re-created through the visual language of the 203 murals found in the territories of the Zapatista Rebel Autonomous Municipalities, and how this identity challenges official Mexican revolutionary imagery and creates a new activist iconography for Zapatista bases and the Zapatista solidarity movement. The work on iconographic creation and restructuring has been theoretically inspired by Geneviève Zubrzycki. The article concludes that the Zapatista murals have common features, the result of an amalgamation of not explicit conceptions of various external and internal subjects that have been confronting the link between art and social transformation in different ways.